2020
DOI: 10.1126/sciimmunol.abc7191
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota–specific IgA + B cells traffic to the CNS in active multiple sclerosis

Abstract: Changes in gut microbiota composition and a diverse role of B cells have recently been implicated in multiple sclerosis (MS), a central nervous system (CNS) autoimmune disease. Immunoglobulin A (IgA) is a key regulator at the mucosal interface. However, whether gut microbiota shape IgA responses and what role IgA+ cells have in neuroinflammation are unknown. Here, we identify IgA-bound taxa in MS and show that IgA-producing cells specific for MS-associated taxa traffic to the inflamed CNS, resulting in a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 74 publications
2
147
0
Order By: Relevance
“…Our observation of expanded and extensively mutated IgA ASCs corroborates previous studies detecting IgA in the CSF (60) and IgA-producing cells in the CSF and MS lesions (23,(61)(62)(63). A recent study found that a proportion of IgA-producing cells in the CSF recognize gut microbiota, and the authors proposed that such cells could represent a population of regulatory cells (23). In the present study, however, we did not detect any distinct regulatory phenotype of IgA-expressing B-lineage cells in the CSF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observation of expanded and extensively mutated IgA ASCs corroborates previous studies detecting IgA in the CSF (60) and IgA-producing cells in the CSF and MS lesions (23,(61)(62)(63). A recent study found that a proportion of IgA-producing cells in the CSF recognize gut microbiota, and the authors proposed that such cells could represent a population of regulatory cells (23). In the present study, however, we did not detect any distinct regulatory phenotype of IgA-expressing B-lineage cells in the CSF.…”
Section: Discussionsupporting
confidence: 92%
“…Further, a number of different B-cell populations in blood seem to have connections to the intrathecal B-cell response (23,55). At the same time, there are evidence that a parallel maturation of B-lineage cells might take place within the CNS: B-cell follicles are present in the meninges of patients with long-standing MS (56,57) and could also be present already at an earlier disease stage (58).…”
Section: Discussionmentioning
confidence: 99%
“…However, commensal-specific IgA does not cross-react with brain tissue. 37 Further studies are required to assess the role of gut-derived IgA-producing cells in MS pathophysiology. Defective IgA binding to gut microbiota in disabled patients with MS might be also related to microbial community alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Gut-derived IgA-secreting plasma cells in the CNS were recently shown to limit neuroinflammation via the production of IL-10 (28). Conversely accumulation of IgAproducing cells reactive with gut bacterial strains associated with MS correlated with acute inflammation in MS (29).…”
Section: The Gut Immune System In the Intricacy Of The Cns Autoimmunitymentioning
confidence: 93%